2021
DOI: 10.1088/1748-9326/abff88
|View full text |Cite
|
Sign up to set email alerts
|

Forests moderate the effectiveness of water treatment at reducing childhood diarrhea

Abstract: Environmental degradation has been associated with increased burden of diseases such as malaria, diarrhea, and malnutrition. As a result, some have argued that continuing ecosystem change could undermine successes in global health investments. Here we conduct an empirical study to investigate this concern. Child deaths due to diarrhea have more than halved since the year 2000, partly due to increased access to improved water, sanitation and hygiene (WASH). We examine how the effectiveness of a water quality tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The frequency of health conditions such as body aches and backache arising from extreme labor (in resources collection) was found higher for the households located away from the forest (Table 1). Because forests are known to contribute to water filtration and purification (Piaggio and Siikamäki, 2021;Rasolofoson et al, 2021), the present study reported a lower frequency of water-borne diseases in households located close to forests, as they were using natural water sources originating from the forests (Table 1). Alike the rest of the Himalayan agricultural system in the Upper Ganga River Basin, agricultural practices in the NDBR area are also connected with the forest resources (Saxena et al, 2005).…”
Section: Discussionmentioning
confidence: 61%
“…The frequency of health conditions such as body aches and backache arising from extreme labor (in resources collection) was found higher for the households located away from the forest (Table 1). Because forests are known to contribute to water filtration and purification (Piaggio and Siikamäki, 2021;Rasolofoson et al, 2021), the present study reported a lower frequency of water-borne diseases in households located close to forests, as they were using natural water sources originating from the forests (Table 1). Alike the rest of the Himalayan agricultural system in the Upper Ganga River Basin, agricultural practices in the NDBR area are also connected with the forest resources (Saxena et al, 2005).…”
Section: Discussionmentioning
confidence: 61%
“…Such a shift in time and energy allocation by women, who are also the primary household caregivers, takes their time and energy away from food preparation, more careful child feeding behaviors, income generation, and health care, and thus can impact the health of household members [39]. As an example for infectious diseases, Rasolofoson et al [40] suggest that good upstream forest conditions can render chlorination more effective at reducing diarrhea prevalence in Haiti and Honduras. They indicated that when forests in upstream areas of watersheds are degraded, the quality of downstream raw water can become poor, which limits the effectiveness of chlorination in dealing with diarrhea [40].…”
Section: Natural Capitalmentioning
confidence: 99%
“…As an example for infectious diseases, Rasolofoson et al [40] suggest that good upstream forest conditions can render chlorination more effective at reducing diarrhea prevalence in Haiti and Honduras. They indicated that when forests in upstream areas of watersheds are degraded, the quality of downstream raw water can become poor, which limits the effectiveness of chlorination in dealing with diarrhea [40]. Preservation of forests through the establishment of protected areas in upstream watersheds was associated with a reduced downstream prevalence of diarrhea on the island of Flores in Indonesia [41].…”
Section: Natural Capitalmentioning
confidence: 99%
See 2 more Smart Citations